The Effect of Alcoholic and Aqueous Extract of Piper nigrum on the Larvae of Culex pipiens molestus Forskal (Diptera:Culicidae) - Aulfat T. Yaseen (مجلة بغداد للعلوم, 2020)
The present study includes the effect of the ethanolic and aqueous extract of Piper nigrum against the third instar of Culex pipiens molestus (Diptera:Culicidae) in different concentrations: 1, 1.5 ppm of ethanolic extracts of Piper nigrum causing 100% mortality of larvae in the second day of treatment, while the concentrations 5% of aqueous extracts of Piper nigrum caused 100% mortality of larvae in the second day of treatment. The concentration 2.5% caused 100% mortality of larvae after four days of treatment. The current study also detected the effect of 0.1% concentration of Piper nigrum aqueous extract. The effect of this concentration has been studied on the growth of the ovaries and their follicles along a period 96 hours after emergence of adult life. The results of this study has clearly shown that the concentration 0.1% of Piper nigrum aqueous extract gave a highly significant inhibitory effect on the growth development of the ovaries and their follicles.